Doing the deals - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
At the first count, more than 100 deals were signed between companies attending the Agro-Ind trade encounters in Dakar, Senegal, in early November 2002. They covered agreements between West African agro-business companies themselves, of whom 230...